2022
DOI: 10.3390/molecules27093025
|View full text |Cite
|
Sign up to set email alerts
|

Extraction, Encapsulation into Lipid Vesicular Systems, and Biological Activity of Rosa canina L. Bioactive Compounds for Dermocosmetic Use

Abstract: Valorization of wild plants to obtain botanical ingredients could be a strategy for sustainable production of cosmetics. This study aimed to select the rosehip extract containing the greatest amounts of bioactive compounds and to encapsulate it in vesicular systems capable of protecting their own antioxidant activity. Chemical analysis of Rosa canina L. extracts was performed by LC-DAD-MS/MS and 1H-NMR and vitamins, phenolic compounds, sugars, and organic acids were detected as the main compounds of the extrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…Elderberries ( Sambucus nigra L.) contain anthocyanins: cyanidin 3-sambubioside and cyanidin 3-glucoside, flavanols: rutin, isoquercetin, astragalin, phenolic acids: chlorogenic and sinapic acid, as well as organic acids [ 26 ]. The most potent antioxidants in rosehip ( Rosa canina L.) are ascorbic acid and polyphenols, specifically cyanidin, catechin, quercetin, and gallic acid [ 27 ]. Rowan fruits ( Sorbus aucuparia L.) contain procyanidin B1, carotenoids (including zeaxanthin and β-cryptoxanthin), catechin and epicatechin, ferulic acid methyl ester, and organic acids [ 28 ].…”
Section: Changes In Chemical Composition and Antioxidant Activitymentioning
confidence: 99%
“…Elderberries ( Sambucus nigra L.) contain anthocyanins: cyanidin 3-sambubioside and cyanidin 3-glucoside, flavanols: rutin, isoquercetin, astragalin, phenolic acids: chlorogenic and sinapic acid, as well as organic acids [ 26 ]. The most potent antioxidants in rosehip ( Rosa canina L.) are ascorbic acid and polyphenols, specifically cyanidin, catechin, quercetin, and gallic acid [ 27 ]. Rowan fruits ( Sorbus aucuparia L.) contain procyanidin B1, carotenoids (including zeaxanthin and β-cryptoxanthin), catechin and epicatechin, ferulic acid methyl ester, and organic acids [ 28 ].…”
Section: Changes In Chemical Composition and Antioxidant Activitymentioning
confidence: 99%
“…Another method used is ethanol extraction which has demonstrated efficacy in extracting higher rates of antioxidant compounds. 15 The concentration of RO in the medication varies depending on the proprietary formulation the rosehip extract used. 16 For example, the FDA found that the maximum use of Rosa canina fruit extract in eye-area skin products was 0.2%, whereas Rosa canina seed extract was used up to 1.5% in lipstick (this is the highest reported concentration).…”
Section: Discussionmentioning
confidence: 99%
“…RO products are typically manufactured through the process of cold pressing the oil from the seed or fruit. Another method used is ethanol extraction which has demonstrated efficacy in extracting higher rates of antioxidant compounds 15 . The concentration of RO in the medication varies depending on the proprietary formulation the rosehip extract used 16 .…”
Section: Discussionmentioning
confidence: 99%
“…To preserve the phenolic and AA contents and evaluate their release and skin retention capacity, different methods have been used (i.e., air-drying, freeze-drying, and lyophilizatio), following encapsulation in nanocarriers including ethosomes, lipososmes, and hyalurosomes. The highest yield extraction (0.4 g extract/g), phenolics (128.6 µg GAE/mg), and AA content (88.8%) were recorded in the lyophilized samples (i.e., appropriate preservation process), following frozen, and dried samples ( Sallustio et al, 2022 ). Loaded liposomes, and hyalurosomes are characterized by significantly increased sizes compared with the loaded ethososmes, due to ethanol’s presence, which enhances the extract’s solubility and enables an easier vesicle encapsulation ( Paiva-Santos et al, 2021 ).…”
Section: Effective Concentrations In Skincare Formulations (Ie Toner ...mentioning
confidence: 99%